1999
DOI: 10.1097/00000539-199910000-00005
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of β-Adrenergic Stimulation on the Length-Dependent Regulation of Myocardial Function in Coronary Surgery Patients

Abstract: This study demonstrated that beta-adrenoreceptor stimulation with dobutamine improved length-dependent regulation of myocardial function assessed during leg elevation in cardiac surgical patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…These findings are consistent with previous reports showing increased diastolic myocardial performance and enhanced myocardial relaxation during β‐adrenergic stimulation in healthy subjects (10, 12, 13, 31, 32). Similar effects and improved ventricular function have been seen in coronary surgery patients with preserved left ventricular performance (33). Conversely, impaired diastolic performance has been shown to be an early sign of dobutamine‐induced myocardial ischemia following myocardial infarction (34) and before percutaneous coronary angioplasty (10, 11).…”
Section: Discussionsupporting
confidence: 62%
“…These findings are consistent with previous reports showing increased diastolic myocardial performance and enhanced myocardial relaxation during β‐adrenergic stimulation in healthy subjects (10, 12, 13, 31, 32). Similar effects and improved ventricular function have been seen in coronary surgery patients with preserved left ventricular performance (33). Conversely, impaired diastolic performance has been shown to be an early sign of dobutamine‐induced myocardial ischemia following myocardial infarction (34) and before percutaneous coronary angioplasty (10, 11).…”
Section: Discussionsupporting
confidence: 62%
“…The evidence to support the use of one inotrope over another has not been rigorously studied and choice is often made on the basis of a more favourable side-effect profile 154,155 , a profile which is dose-dependant. Impairment of diastolic relaxation is a common feature after separation of CPB 156 and recently both dobutamine and milrinone have been shown to have favourable effects on the rate of myocardial relaxation post-CPB 157,158 resulting in improved diastolic and systolic cardiac performance. For this reason dobutamine is viewed by many as a favourable initial inotropic therapy.…”
Section: Levosimendan In Cardiac Surgerymentioning
confidence: 99%
“…At least 10 consecutive beats were taken for the calculation of R. Sample correlation coefficients of the end‐systolic pressure –τ relationships yielded values of r > 0.92 in all patients. Previous reports have indicated that such analysis provides accurate information on systolic and diastolic function and allows assessment of the functional reserve capacity of the left ventricle under various circumstances [15–22]. Arterial and mixed venous blood samples were taken before and 5 min after haemodilution and analysed for calculation of oxygen transport and related variables.…”
Section: Methodsmentioning
confidence: 99%